Ranking Business and Economics Journals in South America Using the Scientific Electronic Library Online (Scielo) - Parada-Daza, V (Taylor and Francis Ltd., 2012)
Access to published research for knowledge creation and education in the administrative science disciplines in South America has been enhanced since the introduction of the Scientific Electronic Library Online (SciELO). Although SciELO has been available as an online journal indexing and publication service since 1998, there have been no bibliometric investigations conducted to identify the quality of journals available through the database. The authors used 4 common ranking measures and an overall index to evaluate the quality of SciELO journals. Age and discipline of the journal seem to be important factors to support impact and ranking. Implications of the findings for business school faculty, administrators, and researchers are discussed. © 2012, Copyright Taylor & Francis Group, LLC.